Uma avaliação da implantação da política de governança digital na Universidade Federal do Ceará - Pires, Tatieures Gomes (2019)
The Digital Governance Policy (PGD), instituted in Brazil in 2016, proposes the use of information and communication technology resources as a facilitator of the approximation between state and society. Its main objective is to align the actions of public agencies with the needs and expectations of citizens, providing more agile and quality services, easy access to public information and new channels for social participation. However, implementing transparent, participatory digital governance is an arduous work that requires commitment and high investments in ICT solutions. The objective of this paper is to evaluate the process of implementation of the Digital Governance Policy at the Federal University of Ceará (UFC). The evaluative perspective adopted was inspired by the critical-dialectical method, which proposes the analysis of the technical and political aspects involved in the context. Through bibliographic research we approach the fundamental elements of the opening of the State and public governance. The methodology adopted in this case study was carried out in three stages: (i) content and policy formulation context analysis; (ii) evaluation of the implementation process at UFC; and (iii) evaluation of the results obtained. The main data collection techniques adopted were, respectively, documentary research, semi-structured interview with the managers responsible for the implementation of the policy in UFC and questionnaire application with the main policy beneficiaries at the University, undergraduate and graduate students. The collected data were analyzed through descriptive statistical analyzes in the light of the theoretical framework. So, the main difficulties and the results obtained by UFC in the implementation of PGD were identified. Among them, we highlight that digital governance did not represent a paradigm change at UFC, but the continuity of the actions that were already being developed. Therefore, UFC was able to implement PGD immediately. Despite this, it was observed that there are still many unmet demands from the student community for digital services; the integration between the UFC systems internally and externally is still insufficient; digital mechanisms for transparency and participation are instituted, but are not widely disseminated; and the community's adherence to participation channels is still low, either due to lack of knowledge or credibility in these instruments.